2021
DOI: 10.1016/j.bbrep.2021.101127
|View full text |Cite
|
Sign up to set email alerts
|

Methylglyoxal attenuates isoproterenol-induced increase in uncoupling protein 1 expression through activation of JNK signaling pathway in beige adipocytes

Abstract: Methylglyoxal (MG) is a metabolite derived from glycolysis whose levels in the blood and tissues of patients with diabetes are higher than those of healthy individuals, suggesting that MG is associated with the development of diabetic complications. However, it remains unknown whether high levels of MG are a cause or consequence of diabetes. Here, we show that MG negatively affects the expression of uncoupling protein 1 (UCP1), which is involved in thermogenesis and the regulation of systemic metabolism. Decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Previous studies have reported that isoproterenol concentrations of 1-10 µM increase the expression of UCP1 and PGC-1α, thereby inducing the browning of white adipocytes in primary cultures derived from human and mouse white adipose tissue [36,45,46]. Furthermore, the browning of white adipocytes into beige adipocytes has been associated with enhanced lipid metabolism and reduced lipid droplet size [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that isoproterenol concentrations of 1-10 µM increase the expression of UCP1 and PGC-1α, thereby inducing the browning of white adipocytes in primary cultures derived from human and mouse white adipose tissue [36,45,46]. Furthermore, the browning of white adipocytes into beige adipocytes has been associated with enhanced lipid metabolism and reduced lipid droplet size [47,48].…”
Section: Discussionmentioning
confidence: 99%